Comparison between Malaysia criminal law and Islamic criminal law on the issue of minor's criminal liability / Lily Suryati Mohd Jamil and Nurzalifah Sulaiman. - Mohd Jamil, Lily Suryati; Sulaiman, Nurzalifah (2008)
There has been a confliction between the applications of the punishment imposed on child between the provision under Malaysian Law and Islamic Law in relation to criminal liability. This situation actually causes confusion especially relating to offences which involved Muslim child in order to determine which law that should be applicable to them. Thus, this project paper seeks to highlight and discuss the different liability imposed under both Malaysian Law and Islamic Law. References also been made to the relevant statutes that govern Malaysian Law and relevant authorities in Quran and Hadith. It must be noted that this project paper only highlight in three offences which includes theft, wine drinking and adultery and all the cases that had been discussed concentrates on the liability imposed on child, and it is significant to show the difference of the law imposed towards the child.